UZBEKISTAN AND THE WORLD COMMUNITY (American Journal of Pedagogical and Educational Research, 2023)
The independence of the state of Uzbekistan, its historical significance, the Declaration of Independence, the foreign policy of Uzbekistan, being a full member of the international community, the participation of the Republic of Uzbekistan in international relations as an independent state, a subject of international law, the strengthening of globalization processes in the whole world, maintaining peace and stability on Earth, issues such as the well-being of the population, its decent standard of living, the role of international organizations in ensuring socio-economic development are covered.